Commissioning progress of the FAST - Jiang, Peng; Yue, YouLing; Gan, HengQian; Yao, Rui; Li, Hui; Pan, GaoFeng; Sun, JingHai; Yu, DongJun; Liu, HongFei; Tang, NingYu; Qian, Lei; Lu, JiGuang; et al. (Science China. Physics, mechanics & astronomy, 2019)
The Five-hundred-meter Aperture Spherical radio Telescope (FAST) was completed with its main structure installed on September 25, 2016, after which it entered the commissioning phase. This paper aims to introduce the commissioning progress of the FAST over the past two years. To improve its operational reliability and ensure effective observation time, FAST has been equipped with a real-time information system for the active reflector system and hierarchical commissioning scheme for the feed support system, which ultimately achieves safe operation of the two systems. For meeting the high-performance indices, a high-precision measurement system was set up based on the effective control methods that were implemented for the active reflector system and feed support system. Since the commissioning of the FAST, a low-frequency ultra-wideband receiver and 19-beam 1.05-1.45 GHz receiver have been mainly used. Telescope efficiency, pointing accuracy, and system noise temperature were completely tested and ultimately achieved the acceptance indices of the telescope. The FAST has been in the process of national acceptance preparations and has begun to search for pulsars. In the future, it will still strive to improve its capabilities and expand its application prospects.